ANALISIS BIOMEKANIKA AYUNAN GOLF DAN RISIKO LOW BACK PAIN PADA PEMAIN GOLF - Paramita, Bunga Listia; Sutarina, Nora (Performa, 2024)
Lateralization in golf can increase muscle imbalances and the risk of low back pain (LBP). This condition needs attention, considering the high prevalence of injuries in the lower back and/or lumbar spine area, 15-35% in amateur golfers. Biomechanics analysis during a golf swing are believed to be one way to prevent LBP. Therefore, this study aims to determine whether the stages of the golf swing can increase LBP risk through an evidence-based case report. The search was carried out on 3 databases, Pubmed, Cochrane, and Scopus, and hand searching with PRISMA from March 3-10th, 2024. 9 articles were obtained which were then reviewed. Flexion speed, length of transition phase, onset time and muscle strength, such as erector spinae (ES), oblique externus (EO), latissimus dorsi (LD), X factor, crunch factor, swing plane and clubhead trajectories, and sequences and angles kinematics during swing can potentially influence the occurrence of LBP. A golfer's posture and muscle imbalances, along with poor swing technique, will increase existing risks. However, there are no conclusive evidence to support the belief that golf swing biomechanical factors are strongly related to LBP. There is a need for further research with better study design related to this in the future.